Layered Double Hydroxide as a Potent Non-viral Vector for Nucleic Acid Delivery Using Gene-Activated Scaffolds for Tissue Regeneration Applications - Lara S. Costard; Domhnall C. Kelly; Rachael N. Power; Christopher Hobbs; Sonia Jaskaniec; Valeria Nicolosi; Brenton L. Cavanagh; Caroline M. Curtin; Fergal J. O'Brien (MDPI AG, 2020)
Nonviral vectors offer a safe alternative to viral vectors for gene therapy applications, albeit typically exhibiting lower transfection efficiencies. As a result, there remains a significant need for the development of a nonviral delivery system with low cytotoxicity and high transfection efficacy as a tool for safe and transient gene delivery. This study assesses MgAl-NO3 layered double hydroxide (LDH) as a nonviral vector to deliver nucleic acids (pDNA, miRNA and siRNA) to mesenchymal stromal cells (MSCs) in 2D culture and using a 3D tissue engineering scaffold approach. Nanoparticles were formulated by complexing LDH with pDNA, microRNA (miRNA) mimics and inhibitors, and siRNA at varying mass ratios of LDH:nucleic acid. In 2D monolayer, pDNA delivery demonstrated significant cytotoxicity issues, and low cellular transfection was deemed to be a result of the poor physicochemical properties of the LDH-pDNA nanoparticles. However, the lower mass ratios required to successfully complex with miRNA and siRNA cargo allowed for efficient delivery to MSCs. Furthermore, incorporation of LDH-miRNA nanoparticles into collagen-nanohydroxyapatite scaffolds resulted in successful overexpression of miRNA in MSCs, demonstrating the development of an efficacious miRNA delivery platform for gene therapy applications in regenerative medicine.